The Influence of Socio-Demographic Factors and Financial Socialisation on Financial Literacy of College Students in Indonesia - Abdul Rahman; Imam Suharto; Puji Hastuti (Journal of Business and Behavioural Entrepreneurship, 2024)
This study aims to explore the level of financial literacy among Indonesian university students as well as the influence of socio-demographic factors and financial socialisation on such literacy. The research method used is quantitative with a survey approach, involving students from various universities in Indonesia. The results showed that on average students were only able to answer 45.39% of financial literacy questions correctly, indicating that the financial literacy of Indonesian university students is at a low to moderate level. The analysis showed that socio-demographic factors such as gender, major in economics and business, and work experience have a significant influence on the level of financial literacy. In addition, financial socialisation through parents was also found to have a significant impact on students' financial literacy. This study emphasises the importance of more effective financial education programmes, both conventional and Islamic, to equip students with the necessary skills to make wise financial decisions. Effective financial socialisation, especially through parental guidance, can significantly improve financial literacy outcomes.